Deconstructing the discourse of divisions: mental boundaries in the divided city of Vukovar - Zorko, M.; Novak, N. (Belgeo, 2020)
This paper seeks to answer to what extent the city of Vukovar is divided and in which way this division is geographically imagined and embedded in everyday life. Since each case of divided cities is driven by different factors and consists of different manifestations, case study design is the most appropriate one for researching micro-divisions in this post-conflict area. The case study of Vukovar is interesting because war legacy influenced new local policies and politics; open border issues affect bilateral relations on State level; and micro-regional frictions show deep identity-based divisions. Regardless of the lack of physical obstacles in the urban structure of the city, the research presents multilevel divisions that are visible in a form of imagined boundaries. Although Vukovar is an ethnically divided city we presume that division(s) lacks any strong geographical (or territorial) aspect. That is why the method of mental mapping on a random based sample of local population is used to compare imagined divisions in everyday life with administrative, ethnical and political ones.